Evaluation of shear bond strength between orthodontic brackets and three aged bulk fill composites = Evaluación de la resistencia de la unión al cizallamiento entre brackets de ortodoncia y tres materiales compuestos de relleno a granel envejecidos - Seyhan Cezairli, Neslihan 1986-
Purpose: The purpose of this study is to evaluate the shear bond strength (SBS) of orthodontic brackets bonded to three different bulk fill composites which were previously aged. Materials and Methods: Three bulk fill composite materials were included in this study (Filtek Bulk Fill, Tetric N-Ceram bulk fill, SureFil SDR bulk fill). Each material group contained 12 samples (n=12); a total of 36 samples were bonded in the same way with maxillary premolar brackets (CB; Avex Mx, OPAL orth.). The same type brackets were bonded on each restored surface made with bulk fill composites. The SBS was examined after storing the specimens for 24 h at 37 ºC indistilled water, followed by thermal ageing (500 cycles between 5 ºC and 55 ºC). Data were analyzed statistically. The numeric data were analyzed using analysis of variance (ANOVA) with Tukey HSD post-hoc tests at α=.05. Results: There were no significant differences among the composite groups (p>0.001). However, SBS values for control group were significantly greater than shear bond strenght values for composite groups (p<0.001). Conclusion: Bond strength of orthodontic brackets on bulk fill composite surfaces was not found adequate. Therefore, this situation leads to bonding failure during orthodontic treatment. The presence of bulk fill composites on the surface to be bonded during orthodontic treatment requires an additional armamentarium.